2000
DOI: 10.1093/pubmed/22.3.343
|View full text |Cite
|
Sign up to set email alerts
|

An international comparison of cancer survival: relatively poor areas of Toronto, Ontario and three US metropolitan areas

Abstract: Systematically replicating a previous Toronto-Detroit comparison, this study's observed consistent pattern of Canadian survival advantage across various cancer sites suggests that their more equitable access to preventive and therapeutic health care services may be responsible for the difference.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
0
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 41 publications
2
43
0
2
Order By: Relevance
“…More than the absolute differential of the socioeconomic level, the influence of the access to healthcare services may explain the inverse relationship between the decrease in late diagnosis and increasing educational levels. 49 Neither can the cultural differences be disregarded, because with them there is the issue of the heterogeneity of access to healthcare and quality treatment. 33 Women of higher socioeconomic status benefit more from the therapy, regardless of the disease stage.…”
Section: Resultsmentioning
confidence: 99%
“…More than the absolute differential of the socioeconomic level, the influence of the access to healthcare services may explain the inverse relationship between the decrease in late diagnosis and increasing educational levels. 49 Neither can the cultural differences be disregarded, because with them there is the issue of the heterogeneity of access to healthcare and quality treatment. 33 Women of higher socioeconomic status benefit more from the therapy, regardless of the disease stage.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported both positive association 10,11 and no association between SES and prostate cancer-specific survival. [12][13][14] Access inequalities to appropriate care and therapy as well as differences in tumor biology are possible explanations for survival differences between SES classes.…”
mentioning
confidence: 99%
“…15 Many previous studies regarding SES and prostate cancer mortality are from North America, particularly from the United States, in which the area code generally is used as surrogate of individual level of SES. 8,9,12,13,16,17 In addition, SES measures may have different meanings in different populations. 15 Furthermore, to our knowledge, few studies to date have evaluated factors impacting social disparities in prostate cancer mortality, such as differences in screening, disease stage at diagnosis, tumor characteristics, and treatment.…”
mentioning
confidence: 99%
“…21,24 About 80% of patients residing in census tracts with high (20% or above) poverty rates lived in the state's four largest cities (Bridgeport, Hartford, New Haven, and Waterbury; Table 1), which also included about 90% of all breast cancer patients who lived in an MUA. Reduced survival rates among lower SES patients with breast and other cancers living in a group of US counties in metropolitan areas (Hartford, CT; San Francisco, CA; Detroit, MI; and Seattle, WA) combined, 25,26 along with small SES gradients in survival in Hawaii and no clear gradient in Toronto (Canada), 16 have suggested a role for differences in health care systems (i.e., health insurance coverage). 16,25,26 For each of the four largest cities in Connecticut, the present study shows an SES gradient (albeit not always statistically significant) in the proportion of patients known to have died (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Reduced survival rates among lower SES patients with breast and other cancers living in a group of US counties in metropolitan areas (Hartford, CT; San Francisco, CA; Detroit, MI; and Seattle, WA) combined, 25,26 along with small SES gradients in survival in Hawaii and no clear gradient in Toronto (Canada), 16 have suggested a role for differences in health care systems (i.e., health insurance coverage). 16,25,26 For each of the four largest cities in Connecticut, the present study shows an SES gradient (albeit not always statistically significant) in the proportion of patients known to have died (Table 1). There was also unexplained variation in the risk ratio for the four cities (relative to the rest of the state) after adjustment for certain patient characteristics (including the SES variable) (Table 3).…”
Section: Discussionmentioning
confidence: 99%